Trading and liquidity in the catastrophe bond market - Markus Herrmann; Martin Hibbeln (Journal of Risk and Insurance, 2022)
We provide first insights into secondary market trading, liquidity determinants, and the liquidity premium of catastrophe bonds. Based on transaction data from TRACE (Trade Reporting and Compliance Engine), we find that cat bonds are traded less frequently during the hurricane season and more often close to maturity. Trading activity indicates that the market is dominated by brokers without a proprietary inventory. Liquidity is high in periods of high trading activity in the overall market and for bonds with low default risk or close to maturity, which results from lower order processing costs. Finally, using realized bid–ask spreads as a liquidity measure, we find that on average, 21% of the observable yield spread on the cat bond market is attributable to the liquidity premium, with a magnitude of up to 1410.167embps for high-risk bonds.
Keywords: 330; alternative risk transfer; catastrophe bonds; liquidity; yield spreads